The role of social brand engagement on brand equity and purchase intention for fashion brands - Sang Vo Minh; Giang Nguyen Huong; Giang Dang Nguyen Ha (Cogent Business & Management, 2022)
This study aims to determine how social brand engagement via social media platforms will have an impact on brand equity and purchase intention towards brands in the field of fashion in the Vietnamese market. The study was carried out a quantitative method, primary data was collected on 637 Vietnamese people aged 18-50~years old. Research results have recognized the direct positive impact of social brand engagement on brand equity and indirect effect on purchase intention. In addition, as a moderator variable, social brand engagement has a positive effect on brand awareness and purchase intention relationship, but this variable is not statistically significant when considering its impact on brand association and purchase intention relationship. These findings contribute to providing information confirming the role of social brand engagement in communication, making a great contribution to brand awareness, but not enough evidence to show the direct impact of social brand engagement on purchase intention. In addition, this study has also established four target customer segments by age in the field of fashion business in Vietnam market with different social brand engagement, perceived brand equity, as well as the intention to purchase different brands are significant. The results help to provide information to identify the target markets for the fashion industry in Vietnam, so that brands have strategic orientations in marketing, selection of target markets, as well as communication strategies and targeting the authentic of social media marketing programs.
Keywords: 650; brand association; brand awareness; brand equity; purchase intention; Social brand engagement